Multifunctional Inhibitor Mixtures for Abating Corrosion on HY80 Steel under Marine Environments. Issue 2 (17th January 2020) - Catubig, R. A.; Neil, W. C.; McAdam, G.; Yunis, R.; Forsyth, M.; Somers, A. E.
Abstract : The commercially available high strength steel, HY80, has been commonly used as part of naval hull construction since the 1950s. Corrosion of HY80 is associated with high costs due to material replacement, labour and lengthy down times of assets. The use of corrosion inhibitors as part of the steel paint system is a cost-effective method of stifling corrosion attack. Incorporation of an antimicrobial component into the inhibitor is also beneficial in combatting microbiologically influenced corrosion (MIC). This work examines the efficacy and mechanisms of corrosion inhibition from mixing lanthanum trans −4-hydroxy cinnamate (La(4OHCin)3 ) with the candidate antimicrobial compounds, imidazolinium trans −4-hydroxy cinnamate (IMI-4OHCin) or cetrimonium nalidixate (CetNal) in artificial seawater. The most effective inhibitor combination was the mixture of La(4OHCin)3 and IMI-4OHCin at their respective solubility limits (La+IMI). Examination of steel surfaces with optical profilometry after a 5 day immersion period concluded that the presence of La+IMI in solution resulted in significant minimisation of material corroded from the steel relative to the uninhibited sample. The inhibition mechanism for this mixture was determined to be predominantly anodic. On the other hand, all solutions containing the CetNal compound appeared to accelerate corrosion attack.